Effects of crude extracts of Allium sativum Linn, Cymbopogon citratus (CD) Stapf and Terminalia catappa L. on rotcausing fungi of Dioscorea species - Okigbo, R.N.; Eme, U.E.; Aseidu, R.; Putheti, R. (2009)
Fungitoxic effects ofAllium sativum Linn., Terminalia catappa L. and Cymhopogoll citratus (DC) Stapf. on four rot-causing fungi (Aspergillus niger, Fusarium oXysporum and Penicillium oxalicum, Botryodiplodia Iheobromae) of stored yam tubers were studied in vitro. Pathogenicity test revealed that A.<,pergillus niger. Botryodiplodia theobromae, Fusarium oxysporum and Penicillium oxalicum induced rot in healthy yam tubers after] 0 days of fe-inoculation, with B. theobromae as the most virulent. Four different concentrations of each plant extract were obtained by blending 25g, 50g, 75g, and 100g of each plant part in 100 ml of sterile distilled water (SDW). A. sativum extracts had effective inhibitions on the mycelial growth of all fungi ranging from 31.1% -92.4%. Extracts of T. catappa and C. citratus showed between slight to moderately effective inhibitions ranging from 3.0% to 46.7% respectively. The effects of T. catappa and C. citratus extracts on the mycelial growth of B, theobromae was stimulatory rather than inhibitory at all concentrations while A. sativum proved just slightly inhibitory at higher concentrations. The most fungitoxic of all the extracts was A. sativum at 10% concentration which showed significant (P < 0.01) inhibitions on all the fungal pathogens investigated indicating its potential as a natural fungicide against rot common in yams while in storage.